Normative Humiliation and Female Voice as Performative Resistance in The Lesson by Sowmya Rajendran (Knowledgeable Research A Multidisciplinary Journal, 2026)
Societies across the world remain structured by inequalities rooted in race, class, caste, and, most persistently, gender, with patriarchal systems relying on shame and humiliation as regulatory tools to discipline women and suppress dissenting voices. This paper examines how such normalized practices of humiliation operate within patriarchal authority and investigates the emergence of female voice as a form of resistance in The Lesson. Drawing on feminist literary theory and Judith Butler’s concept of gender performativity, the study employs close textual analysis to examine how humiliation is institutionalized as a normative disciplinary practice and internalized as moral conformity. The analysis reveals that female voice in the narrative does not merely articulate personal suffering but actively disrupts the moral legitimacy of patriarchal power by rejecting shame as a naturalized condition. Through acts of articulation, questioning, and refusal, female agency transforms from passive subversion into conscious resistance. The study concludes that The Lesson foregrounds female voice as a political and ethical force that challenges normative humiliation an destabilizes entrenched patriarchal control, contributing to feminist discussions on power, discipline, and women’s agency in contemporary literature.
Keywords: Gender Performativity, Humiliation, Resistance, Normative Discipline.